Pop art, hybrid cultures and intangible cultural heritage in El Salvador. The particular case of “Chirajito” clown - Melara Martínez, Mario Alberto; Becario Organización de Estados Americanos (OEA) (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2014)
This article makes a reflection from Intangible cultural heritage about a popular artistic expression, that, for such a long timehas gained validity and reconnaissance among Salvadorian community but it is out of official artistic parameters because it’sa non academic character. From the question, is or not Chirajito clown Salvadorian intangible cultural heritage? is tackle thehistoric happening of Clown figure, the gaps in Salvadorian cultural legislation, generic concepts of international conventions,the hybridization that suffer in space and in time this kind of artistic expressions as a globalized but at the same time local, andurban product. Furthermore, the figure of Chirajito clown and his author Arístides Alfaro Samper are tackled from one of themost historic periods of his career. 1980´s decade. The civil war left a mark in Salvadorian’s collective memory. Chirajito, withhis appearance in Jardin Infantil´s program did it too. What is preserved to the future? What is forgotten? That is discussed inthis article. From the supposition that Salvadorians want to activate and preserve this character´s memory, the author giveshis own conclusions and proposes ways to do it.